Role of Brownian motion and Néel relaxations in Mössbauer spectra of magnetic liquids - A. Ya. Dzyublik; I. E. Anokhin; V. Yu. Spivak (Ядерна фізика та енергетика)
The absorption cross-section of Mössbauer radiation in magnetic liquids is calculated, taking into consideration both translational and rotational Brownian motion of magnetic nanoparticles as well as stochastic reversals of their magnetization in the absence of an external magnetic field. The role of Brownian motion in ferrofluids is considered in the framework of the diffusion theory, while for the magnetorheological fluids with large nanoparticles, it is done with the aid of Langevin's approach. For stochastic rotation, we derived the equation analogous to Langevin's one and found the corresponding correlation function. In both cases, simple rotational correlation functions are obtained in the approximation of small rotations during the lifetime of the excited Mossbauer nuclei. Influence of the Néel's relaxations is considered in the framework of the Blume - Tjon model.